Estudo fluidodinâmico e influência de dispositivos internos instalados em separadores atmosféricos gravitacionais de petróleo - tanques de água livre - Aragão Júnior, Mabel Albuquerque (2011)
Producing oil is a complex process where the fluids existing in a deep layer of the subsurface must be raised to the surface through the production well, where oil and natural gas are handled. The primary treatment of oil is basically done in two stages, the separation of gaseous and liquid phase separation, oil, water and other contaminants. Production facilities in offshore fields, which concentrates the largest and most recent discoveries of oil, the relatively small space in the production platforms has led to the employment of more compact process equipment. Pressure vessels are used in the separation of liquid phases, oil and water, imposing greater turbulence to fluids contributing to the formation and stabilization of emulsions of oil. This work aims at using CFD (Computational Fluid Dynamics) a software tool to visualize the behavior of fluid flow to analyze the dynamics of atmospheric flow in gravitational separators. To evaluate the influence of some internal atmospheric gravity separator tank known as Free Water Tank and how some its dimensions interfere with the gravitational separation. We restrict our analysis in a qualitative view of fluid dynamics in the gravitational separator and the occurrence of atmospheric phenomena that may influence its efficiency. For the separator model we could highlight the importance of the inductor tube, since the velocity profiles produced show the influence of its dimensions in the functionality of the equipment. Therefore the gravitational separators type, Free Water Tank height and diameter of the tube inducer, greatly influence the performance of the gravitational separator, thus, appears that supporting devices should be objects of analysis also at existing facilities.